The Effect of Halal Tourism Development on Tourist Satisfaction: Integrating Quantitative and Qualitative Approaches in Kampung Landeuh Baduy Mualaf, Lebak, Banten - Selasi, Dini; Pratiwi, Ayu Alfiani; Suharto, Taufik Hidayat; Vidiati, Cory (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
Satisfaction is important in the future development of halal tourism. This study aims to analyze the effect of halal tourism development on tourist satisfaction. The research method used mixed methods, where quantitative data was obtained from 100 tourist respondents and qualitative data was collected through observation and interviews with tourism managers, communities, and tourists. The data was then analyzed using simple linear regression and source triangulation. The results of this study can be seen from β = 0.889, r² = 78.5%, p < 0.001, which indicate that the development of halal tourism has a positive effect on tourist satisfaction. The factors that influence this are halal facilities, quality services, storytelling, digital marketing, and spiritual and educational experiences, which create a positive image, potential for repeat visits, and word-of-mouth promotion. The development of halal tourism is carried out with an experiential approach by exploring various local cultures, spiritual experiences, cultural education with sharia-based management, and halal tourism experiences are not only about the attractiveness of tourist locations but must also be supported by the availability of halal facilities and infrastructure, quality halal services, educational tourism, and traditional culture. Marketing strategies for experience-based development can be implemented by strengthening cultural and religious storytelling, halal tourism packages, utilizing digital marketing and tourist reviews, and improving facilities and services. This research contributes to integrating religious and cultural aspects, as well as community participation, which play an important role in the development of halal tourism based on tourist experiences. The implications can be utilized to create SOPs for halal tourism services, develop digital marketing, and strengthen the involvement of all parties for the sustainability of halal tourism